Socio Demographic Factors Influencing the Income of Native Chicken Farming in Rural Area of Ciamis Regency - Setiana, Lucie; Sugiarto, Mochamad; Djatmiko, Oentoeng Edy (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
Sentul chicken is one of indigenous poultries maintained by most people in Ciamis Regency, West Java Province. This study aimed at determining the influence of socio demographic factors on the income generated from Sentul chicken farming in Ciamis Regency. A survey method was conducted to the members of seven farmer groups institutionally assisted by the Ciamis Regency Government Unit. The descriptive statistics and multiple linear regression analysis were used to describe the profile of respondents and to analyze the influence of socio demographic factors on the income generated from Sentul chicken farming. The results showed that the farmers’ length of education was 11.8 years with 5.8 years experience raising the Sentul chicken while the farm size was averagely 9 heads of chicken. The Sentul chicken farmmaintained in 70 days with semi-intensive production system has generated income ranging from IDR 756,000 to IDR 19,900,000. Farming experience and farm size significantly influenced the income generated from Sentul chicken farming. Increase the farming experience of Sentul chicken farmers and enlarging Sentul chicken farm size with semi-intensive production system may improve the income generated from Sentul chicken farming in Ciamis Regency.